"We Have All the Data in One Place": Examining Principals' Use of a Data Warehouse During an Academic School Year. (June 2021) - Drake, Timothy A.
In this article, I describe how principals accessed teacher and student data on a centralized data warehouse (DWH) during an academic school year. I found that principals did not use the DWH very often during the year. When logged on, principals most often looked at reports on student achievement, teachers' performance, or student demographics. Principals' use also seemed to be influenced by the school calendar and the release of student and teacher data, along with personal and organizational characteristics.